STUDY OF VITAMINS CONTAINED IN MELON PEEL AND ITS USE IN FOLK MEDICINE (Scientific journal of the Fergana State University, 2023)
The article examines the vitamins in the chemical composition of melon peel by high-performance liquid chromatography (HPLC) method. According to the test results, the amount of vitamins contained in the melon peel: B4-63 mg, B12-7.3 mg, B2-2.96 mg, E2-18 mg, B6-2.03 mg, B5-0.75 mg, B9- 0.64 mg, C-0.32 mg, K-7.32 mg, and in addition to vitamins, β-carotene - 9 mg was found. Melon skin is rich in vitamins, it contains a lot of biologically active substances, and it is highlighted that it can be widely used in folk medicine as a food additive in the future.